Effectiveness of tofacitinib in patients with ulcerative colitis: an updated systematic review and meta-analysis of real-world studies - Chuan Wan; Chien-Hung Lin; Wen-Sheng Liu; Hsin-Hui Wang (BMJ Open Gastroenterology)
Objectives This study aimed to evaluate the real-world effectiveness of tofacitinib for treating moderate-to-severe ulcerative colitis (UC).Design Systematic review and meta-analysis.Data sources PubMed, EMBASE and Cochrane CENTRAL databases were searched from inception up to 18 July 2023. Reference lists of included studies were manually searched to identify potentially relevant studies not found in the databases.Eligibility criteria Eligible studies included real-world observational studies, reported in English, on patients with moderate-to-severe UC treated with tofacitinib, defined by the Partial Mayo Score. Excluded were clinical trials, reviews, letters, conference abstracts, case reports and studies involving patients with mixed Crohn’s disease.Data extraction and synthesis Two independent reviewers extracted data and recorded it in Excel. Quality assessment was performed using the Newcastle-Ottawa scale. Meta-analysis was performed using random-effects models due to high heterogeneity across studies.Results 19 studies containing a total of 2612 patients were included. Meta-analysis revealed that clinical response rates were 58% at week 8, 61% at weeks 12–16, 51% at weeks 24–26 and 51% at week 52. Clinical remission rates were 39% at week 8, 43% at weeks 12–16, 40% at weeks 24–26 and 43% at week 52. Corticosteroid-free clinical remission rates were 33% at week 8, 37% at weeks 12–16, 32% at weeks 24–26 and 40% at week 52.Conclusion This meta-analysis of real-world studies indicates that treatment of UC with tofacitinib is associated with favourable clinical response and remission rates in the induction and maintenance phases.